Fatores de risco relacionados ao estresse materno e indicadores neurocomportamentais de recém-nascidos pré-termo em unidade de terapia intensiva neonatal - Ramos, Bruna Abreu (2023)
Introduction: Prematurity is the main cause of hospitalization in the Neonatal Intensive Care Unit, being considered an important factor for adverse infant outcomes, in terms of quality of life. Objectives: To analyze maternal stress and its correlation with neonatal neurobehavioral indicators and to identify the main risk factors (maternal and neonatal) associated with preterm newborns in neonatal intensive care units. Methods: The total study sample consisted of 251 preterm, low birth weight newborns and their respective mothers, who were admitted to the Neonatal Intensive Care Unit and the Neonatal Intermediate Care Unit of a Public Maternity Hospital in the city of Goiania ( GO). An analysis of medical records was performed, the parental stress assessment scale (PSS: NICU) was applied, and finally, the neurobehavioral assessment instrument for preterm newborns (NAPI) was used. For the statistical analysis of the total sample, the Spearman correlation test was performed (p < 0.05) and for the logistic regression analysis, the sample n of 165 participants was used based on the exclusion criteria, in order to test the possible factors of risk for maternal stress. In all analyses, p < 0.05 was considered. Results: Considering the outcome on maternal stress, the level of stress was assessed as moderate among mothers. The subscale that presented the highest level of stress was "Change in the Role of Mother" and the one with the lowest level of stress was "Sounds and Images", with total scores ranging from "little stressful" to "very stressful". . The higher the stress level on the item “the other sick babies in the room” the lower the leg resistance performance (p <0.049). It was also observed that neonatal and maternal risk factors did not present an outcome with maternal stress. The respiratory rate variable of 49.8 bpm and the scarf signal of 60.11 at the time of the neonatal neurobehavioral assessment, was shown to be a protective factor for maternal stress (p <0.05) and adjusted OR <1. Conclusion: The mothers considered the experience of having a newborn hospitalized in the Neonatal Intensive Care Unit moderately stressful. Weak correlations were identified between maternal stress and neonatal neurobehavioral indicators. No relationship was found between neonatal and maternal risk factors for maternal stress, but muscle tone (scarf sign) and respiratory rate at the time of assessment behaved as protective factors for maternal stress.